Simulation and in vivo experimentation predict AdamTS‐A location of function during caudal visceral mesoderm migration in Drosophila. Issue 7 (24th January 2022) - Hamilton, William C.; Stolarska, Magdalena A.; Ismat, Afshan
Abstract: Background: Caudal visceral mesoderm (CVM) cells migrate as a loose collective along the trunk visceral mesoderm (TVM) and are surrounded by extracellular matrix (ECM). In this study, we examined how one extracellular protease, AdamTS‐A, facilitates CVM migration. Results: A comparison of mathematical simulation to experimental results suggests that location of AdamTS‐A action in CVM cells is on the sides of the cell not in contact with the TVM, predominantly at the CVM‐ECM interface. CVM migration from a top‐down view showed CVM cells migrating along the outside of the TVM substrate in the absence of AdamTS‐A . Moreover, overexpression of AdamTS‐A resulted in similar, but milder, mis‐migration of the CVM. These results contrast with the salivary gland where AdamTS‐A is proposed to cleave connections at the trailing edge of migrating cells. Subcellular localization of GFP‐tagged AdamTS‐A suggests that this protease is not limited to functioning at the trailing edge of CVM cells. Conclusion: Using both in vivo experimentation and mathematical simulations, we demonstrated that AdamTS‐A cleaves connections between CVM cells and the ECM on all sides not attached to the TVM. Clearly, AdamTS‐A has a more expansive role around the entire cell in cleaving cell‐ECM attachments in cells migrating as a loose collective. Key Findings: AdamTS‐A functions differently in the CVM than in the salivary gland